Does degree completion improve non-cognitive skills during early adulthood and adulthood?. (February 2019) - Oi, Katsuya
Abstract: Introduction: Non-cognitive skills, particularly in terms of risk-aversion, future-orientation, and conscientiousness, grow with age, and this phenomenon is known as personality maturation. However, significant variability in maturation among individuals exists. The technology of cognitive/non-cognitive skill formation suggests that the growth of non-cognitive skills is contingent on cognitive skills or human capital in general. The completion of formal education is a quintessential form of human capital. The aim of this study is to test whether formal education indeed facilitates the improvement of non-cognitive skills during early adulthood and adulthood.] Methods: I used data from the National Longitudinal Study of Adolescent to Adult Health. The study sample consists of 9291 individuals, representative of U.S. adolescents in grades 7 through 12 in 1994. The longitudinal design of the data allowed the repeated measurement of their non-cognitive skills in adolescence (age < 18), early adulthood (between 18 and 25) and then in adulthood (>25). I used Latent Score Difference modeling to examine whether advancement in formal education through degree completion predicts within-individual change in non-cognitive skills in early adulthood and adulthood. Results: A steady increase in non-cognitive skills beyond adolescence was found. Independently of academic engagement during high school, parental socio-economic status, and adolescent non-cognitive skills, degree completion reported in early adulthood coincides with gains in non-cognitive skills since adolescence, and this positive feedback repeats itself in adulthood. Conclusions: Continued schooling facilitates personality maturation beyond adolescence. Given the profound effects of non-cognitive skills on various life outcomes, educational opportunities could alleviate social stratification.